COMPARATIVE ANALYSIS OF THE EXPORT POTENTIAL OF THE REPUBLIC OF UZBEKISTAN WITHIN THE FRAMEWORK OF THE EAEU - Nigora Gulomova (Journals Park Publishing, 2023)
The significance and function of export potential lie in its ability to serve as a crucial measure of competitiveness, affirming genuine competitive advantages. Additionally, it acts as an instrument for advancing national interests in the global economic landscape. This article provides a comparative analysis of Uzbekistan's export potential within the Eurasian Economic Union (EAEU). The article examines foreign trade relationships of Uzbekistan within this regional economic bloc.
Keywords: Foreign trade, export, EAEU, trade balance, economic development, turnover, export potential.